Delayed Posterior Reversible Leukoencephalopathy Syndrome Triggered by FLOT Chemotherapy - Gandini, Jordi; Manto, Mario; Charette, Nicolas (Frontiers in Neurology, 2020)
Posterior reversible encephalopathy syndrome (PRES) is a potentially severe disorder of the autoregulation of cerebral perfusion. The major clinical manifestations are headache, seizures, altered mental status and visual loss. The typical radiological finding is vasogenic edema predominating in white matter of occipital and parietal lobes. PRES is increasingly recognized as a clinic-radiological entity due to improvements and fast availability of brain imaging, especially magnetic resonance imaging (MRI). We present the exceptional case of a 67-year-old female patient with a gastric adenocarcinoma treated by FLOT chemotherapy (5-fluouracil /oxaliplatin/ docetaxel/folinic acid). Two months after the unique administration of FLOT regimen, she developed sudden posterior headache and visual loss. Blood pressure values were normal. Cerebral tomography showed ischemic-like occipital bilateral lesions and angiographic sequences revealed a breakdown of blood-brain-barrier (BBB). MRI demonstrated bilateral parieto-occipital hyperintensities in T1/T2-weighted images and in fluid attenuated inversion recovery (FLAIR) sequences. After injection of gadolinium a linear enhancement of cortex was observed. She was treated with oral nimodipin. Follow-up was characterized by permanent visual sequelae and tetraparesis. PRES represents an urgent neurological condition. Our observation highlights that PRES should be considered in patients under chemotherapy, even when the blood pressure remains within normal range. This is the first report of PRES triggered by FLOT chemotherapy and with a silent window of 2 months between chemotherapy and PRES, widening further the spectrum of chemotherapy-induced PRES. Our case also questions the need for preventive therapies after administration of chemotherapies causing PRES.